Delayed reconstruction following incarceration of the medial epicondyle in the elbow joint: a case report and review of the literature - Lotz, Benedict; Akilapa, Oluwasegun; Karthik, Karuppaiah (Journal of bone and joint surgery. Case Connector, 2018)
Case:Neglected medial epicondylar fractures with intra-articular incarceration are uncommon. At 6 weeks after an elbow dislocation, an 11-year-old child was referred to our unit with painless, restricted range of motion. Clinical assessment and radiographic imaging revealed an incarcerated medial ep
Publication Date: 2018/07/01
Gesehen am 12.07.2019